Representasi Pernikahan Beda Agama dalam Film Komang : Analisis Semiotika Ferdinand de Saussure - Dewa Ayu Triadinda Cahya Subandi; Kadek Adyatna Wedananta; Putri Ekaresty Haes; Ni Putu Yunita Anggreswari (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the meaning of interfaith marriage in the film Komang using Ferdinand de Saussure's semiotic theory. This theory emphasizes the relationship between signifier and signified as well as the concepts of langue and parole to explain the interaction between social systems and individual expression. The results of the analysis show that the visual, verbal, and symbolic signs in the film represent the clash between love and belief. Scenes such as the initial meeting at a cultural festival, family rejection, and symbolic marriage become a form of negotiation between social values and personal freedom. This film affirms that interfaith marriage in Indonesia can only be accepted through compromise with the religious norms of the majority, but still presents a message of tolerance through symbols of cultural harmony. Therefore, the film Komang is not just a romantic narrative, but a social reflection on the relationship between religion, culture, and love in a pluralistic society.